PROSES PERTUMBUHAN DAN HASIL DUA VARIETAS TANAMAN KEDELAI (Glycine max (L.) Merrill) DENGAN PERLAKUAN TIGA TIPE JARAK TANAM: Kata kunci: Jarak tanam, varietas, kedelai, pertumbuhan, hasil - Afringga Rohmawan; Siswadi Siswadi; Sumarmi Sumarmi (Innofarm:Jurnal Inovasi Pertanian, 2023)
Research on  the  study  of  plant  spacing  on  the  growth  and  yield  of  two  varieties  of  osoybean  plants  was  carried  out  in  May–July  o2022,  at  the  Tohudan  Food  Crops  and  Horticultural  Seed  Garden,  Karanganyar.  This  study  aims:  to  determine  the  effect  f  spacing  on  the  growth  and  yield  of  two  varieties  of  soybean  plants.  This  study  used  a  Completely  Randomized  Block  Design  (RAKL)  which  was  arranged  in  a  factorial  manner  with  2  treatment  factors,  namely  spacing  (J)  and  variety  (V)  which  produced  6  combinations.  J1:  20  cm  x  20  cm  spacing,  J2:  20  cm  x  30  cm  spacing,  J3:  o20  cm  x  40  ocm  spacing,  oV1:  Anjasmoro  ovariety,  V2:  Biosoy  variety.  Observations  were  made  in  the  treatment  plot.  To  find  out  whether  there  was  an  oeffect  of  spacing  treatment  on  two  varieties  of  soybean  plants,  then   the  observed  data  were  analyzed  using  analysis  of  variance.  Meanwhile,  to  find  out  the  significance  of  the  treatment,  the  BNJ  test  was  used  at  the  5%  level.  The  results  showed  (1)  the  height  of  soybean  plantof  the  Anjasmoro  variety  othe  ospacing  oof  othe  onon-Anjasmoro  variety  range  from  o105,3  cm  to  108,5.  Affet  plant  height  on  Anjasmoro  variety.  The  height  variety  Biosoy  variety  ranged  from  81,67  –  92,25  cm.  (2)  Stem  diameter  of  soybean  varieties  Anjasmoro  and  oBiosoy  oranged  ofrom  o8,09  o–  o8,92  omm,  spacing  was  not  significantly  different  for  all  treatments.  (3)  oThe  number  of  pods  per  plant  on  the  Anjasmoro  variety  with  a  spacing  of  20  cm  x  40  cm  (J3)  reached  134,25  pods,  the  heighest  compared  to  other  treatments.  (4)  The  weight  oof  100  soybean  seeds  of  the  Biosoy  ovariety  showed  a  yield  of  22.37  –  23.56  grams  which  was  better  than  the  Anjasmoro  variety,  ranging  from  15.63  –  16.07  grams